Limit analysis of earthquake-induced landslides considering two strength envelopes - D. Wu; Y. Wang; X. Chen (Natural Hazards and Earth System Sciences)
Stability analysis of soil slopes undergoing earthquake remains an important research aspect. The earthquake may have some different effects on slope stabilities associated with nonlinear and linear criteria, which need to be further investigated. For homogeneous soil slopes undergoing earthquakes, this paper established the three-dimensional (3D) failure mechanisms with the power-law strength envelope. The quasi-static method was employed to derive the work rate done by the earthquake in limit analysis theory. The critical heights and critical slip surfaces associated with nonlinear and linear criteria were obtained for four slope examples undergoing different seismic loads. Comparisons of the nonlinear and linear results illustrated that two critical inclinations (resulting from the overlap of nonlinear and linear results) both decrease as the seismic force increases, but their difference is almost constant. For steep slopes, the use of linear strength envelope can lead to the non-negligible overestimation of slope critical height. This overestimation will become significant with the increase in seismic force, especially for the steeper slope with a narrow width. Since the seismic force has a positive influence on equivalent internal friction angle, the critical slip surface for the slope-obeying nonlinear envelope tends to be slightly deeper as the earthquake becomes stronger. For steep soil slopes undergoing the earthquake, the development of 3D stability analysis with a nonlinear yield criterion is necessary and significant. These findings can provide some references for the risk assessment and landslide disaster reduction of soil slopes.